2nd law analysis of Portuguese municipal solid waste gasification using CO2/air mixtures. (July 2017) - Couto, Nuno; Silva, Valter; Cardoso, J.; Rouboa, Abel
Highlights: Assessment of gasification for MSW treatment was studied. Mixtures of CO2 and air as gasifying agent were investigated. Previously developed CFD model was used to predict gasification process. Influence of operational conditions on exergy values was investigated. Tar mitigation and carbon dioxide conversion were examined. Abstract: Urbanization, mainly caused by population growth and industrialization, is causing serious environmental problems. Municipal solid waste (MSW) is one of the major challenges facing the world today. In Portugal the growing volume of MSW has become a central problem for municipalities, due to lack of space and the high costs to solve it. Gasification is starting to be considered as a possible alternative when dealing with municipal wastes. However, first is necessary to overcome some concerns related to the process, such as tar mitigation and carbon dioxide emissions. The presented study focuses on a second law analysis conducted on Portuguese MSW gasification using carbon dioxide and air mixtures. To do so, a previously developed numerical model, validated using data from a semi-industrial plant, was used to assess carbon dioxide injection. First, influence of operational conditions on syngas exergy values was studied. Exergy values increased close to 6% when equivalent rate was increased from 0.15 to 0.25, steadily dropping with further increase. On the other hand, exergy values appear to steadily increase with carbon dioxide addition (14% when increased from 0 to 1) and reactor temperature (40% when increased from 700 to 900 °C). Then, the influence of temperature and CO2 /MSW ratio on exergy efficiency, tar efficiency and carbon dioxide conversion was investigated. Results showed that both parameters have a positive effect on exergy efficiency. Conversely, CO2 /MSW ratio and gasification temperature lead to decreases in both tar exergy efficiency and in carbon dioxide.